Ultrasensitive Wearable Pressure Sensors Based on Silver Nanowire-Coated Fabrics - Yunlu Lian (Nanoscale Research Letters, 2020)
Abstract Flexible pressure sensors have attracted increasing attention due to their potential applications in wearable human health monitoring and care systems. Herein, we present a facile approach for fabricating all-textile-based piezoresistive pressure sensor with integrated Ag nanowire-coated fabrics. It fully takes advantage of the synergistic effect of the fiber/yarn/fabric multi-level contacts, leading to the ultrahigh sensitivity of 3.24 × 105 kPa−1 at 0–10 kPa and 2.16 × 104 kPa−1 at 10–100 kPa, respectively. Furthermore, the device achieved a fast response/relaxation time (32/24 ms) and a high stability (> 1000 loading/unloading cycles). Thus, such all-textile pressure sensor with high performance is expected to be applicable in the fields of smart cloths, activity monitoring, and healthcare device.